2015
DOI: 10.1007/s10862-015-9519-5
|View full text |Cite
|
Sign up to set email alerts
|

Adult ADHD: Associations with Personality and Other Psychopathology

Abstract: The goals of this study were to explicate adult ADHD's relations with personality at both the domain and facet levels and to examine its associations with other psychological symptoms. Community members (N=294) completed measures assessing ADHD inattentive and hyperactive/ impulsive symptoms, five-factor model personality domains and facets, and other internalizing and externalizing symptoms. Inattentiveness showed strong negative relations with conscientiousness and extraversion and strong positive relations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 54 publications
3
24
1
3
Order By: Relevance
“…No specific hypothesis was made regarding agreeableness or openness.ADHD-IN symptoms would be uniquely associated with higher BIS and neuroticism, as well as lower conscientiousness. We expected ADHD-IN to be unassociated or negatively associated with BAS, extraversion, agreeableness, and openness (Hundt et al, 2008; Knouse et al, 2013; Nigg et al, 2002; Parker et al, 2004; Rabiner et al, 2008; Stanton & Watson, 2016). ADHD-HI symptoms would be uniquely associated with higher BAS, extraversion, and neuroticism, as well as lower agreeableness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No specific hypothesis was made regarding agreeableness or openness.ADHD-IN symptoms would be uniquely associated with higher BIS and neuroticism, as well as lower conscientiousness. We expected ADHD-IN to be unassociated or negatively associated with BAS, extraversion, agreeableness, and openness (Hundt et al, 2008; Knouse et al, 2013; Nigg et al, 2002; Parker et al, 2004; Rabiner et al, 2008; Stanton & Watson, 2016). ADHD-HI symptoms would be uniquely associated with higher BAS, extraversion, and neuroticism, as well as lower agreeableness.…”
Section: Introductionmentioning
confidence: 99%
“…We expected ADHD-HI to be unassociated or negatively associated with BIS, as well as unassociated with openness. No specific hypothesis was made regarding conscientiousness (Hundt et al, 2008; Knouse et al, 2013; Mitchell, 2010; Mitchell & Nelson-Gray, 2006; Nigg et al, 2002; Parker et al, 2004; Rabiner et al, 2008; Stanton & Watson, 2016). Anxiety/depression symptoms would be uniquely associated with higher BIS and neuroticism, as well as lower BAS, extraversion, and conscientiousness.…”
Section: Introductionmentioning
confidence: 99%
“…3 A number of studies examining psychopathology structure also support this classification of ADHD symptoms as externalizing in nature, 11 with some proposals created to inform knowledge of the DSM-5 metastructure describing ADHD as overlapping more closely with other externalizing disorders than with NDDs such as ASD. 12 However, ADHD symptoms also show meaningful cross-sectional and longitudinal associations with symptoms such as dysphoric mood that are more indicative of internalizing than externalizing pathology, 13,14 which has led to proposals suggesting that experiences of negative affect and difficulties regulating them may be core ADHD features. 15,16 These discrepancies regarding the optimal classification of ADHD symptom dimensions, as well as the lack of understanding regarding classification of ASD dimensions, may be exacerbated by many prior studies focusing solely on global, composite diagnostic ratings rather than conducting analyses using specific symptom scores that may show differential associations with personality and other forms of psychopathology (e.g.…”
mentioning
confidence: 99%
“…It was mostly associated with the externalizing spectrum (i.e., aggression and antisocial behavior) (Kotov et al, 2010;Mezquita et al, 2015), and also with the p factor (Caspi et al, 2014;Castellanos-Ryan et al, 2016;Etkin et al, 2020;Mann et al, 2020). Our results also showed, as predicted, that the conscientiousness onset was negatively associated with the externalizing factor (De Bolle et al, 2012;Mann et al, 2020), hyperactivity/attention problems (Mann et al, 2020;Stanton & Watson, 2016), and the p factor (Etkin et al, 2020;Mann et al, 2020), although we found a significant association with scales pertaining to the internalizing factor too. Moreover, conscientiousness' growth was negatively associated with p and hyperactivity/attention problem factors, which differs from Mann et al (2020).…”
Section: Discussionsupporting
confidence: 68%